(untitled) - Hsueh, Tien-tung (Hong Kong, 1991)
The Management of Enterprises in the People's Republic of China aims to contribute to the knowledge base of management within the Chinese context. The book begins with a mapping of research on management in PRC, and offers theoretical insights for cross-context, institutional, and behavioral studies. It then reports the results of fourteen empirical studies of management issues in the PRC firms. The issues studied include SOE transformation, globalization, governance, employment relationships, managerial networks, corporate culture and leadership. Also included are studies on the knowledge management process and management team characteristics of high technology firms. The methods of study include large-scale surveys, case studies, and interviews. The contributors are international experts in Chinese management research. Finally, we offer executive perspectives on several successful firms operating in China through interviews with their CEOs.
Keywords: Trung Quốc,China; Điều kiện kinh tế,Economic conditions